Typhlachirus lipophthalmus, a rare eye-less sole from Borneo (Teleostei: Soleidae) - Tan, Heok Hui; Jongkar, Grinang (Verlag Dr. Friedrich Pfeil, München, Germany, 2020)
An example of the eye-less sole, Typhlachirus lipophthalmus, was collected from a tidal section of the Sadong River in Sarawak, Malaysian Borneo, in January 2018. It is apparently the second known record of this species since its description in 1882. A description based on selected meristic and morphometric data gathered from the speci-men, supported by radiographs and photographs of it, as well as notes on its capture and habitat, are presented.